First Description of the Female of the Trinidadian Theraphosine Spinosatibiapalpus trinitatis (Pocock, 1903) (Araneae: Theraphosidae) † - Sherwood, Danniella; Guadanucci, José Paulo Leite [UNESP]; Gabriel, Ray (MDPI, 2022)
The hitherto unknown female of the theraphosine Spinosatibiapalpus trinitatis (Pocock, 1903) is herein described based on the paralectotype series of the schismatotheline Neoholothele incei (F. O. Pickard-Cambridge, 1899) housed in the collections of the Natural History Museum, London.
Keywords: morphology; museums; spermathecae; tarantula; taxonomy